Lipid accumulation by oleaginous and non-oleaginous yeast strains in nitrogen and phosphate limitation - Kolouchová, Irena; Maťátková, Olga; Sigler, Karel; Masák, Jan; Řezanka, Tomáš (Folia microbiologica, 2016)
We investigated the possibility of utilizing both oleaginous yeast species accumulating large amounts of lipids (Yarrowia lipolytica, Rhodotorula glutinis, Trichosporon cutaneum, Candida sp.) and traditional biotechnological non-oleaginous ones characterized by high biomass yield (Kluyveromyces polysporus, Torulaspora delbrueckii, Saccharomyces cerevisiae) as potential producers of biofuel-utilizable and nutritionally valuable lipids. The main objective was to increase lipid accumulation by increasing C/P ratio together with higher C/N ratio, while maintaining high biomass yield. The C/N ratio of 30 was found to lead to higher biomass content and the total lipid content increased significantly with higher C/P ratio. With higher ratios of both C/N and C/P, the content of monounsaturated fatty acids (FAs) in cell lipids increased while polyunsaturated FAs decreased. Oleaginous yeast species had a lower proportion of unsaturated FAs (approx. 80 %) than non-oleaginous strains (approx. 90 %). At a C/N ratio of 30 and C/P ratio 1043, T. cutaneum produced a high amount of ω-6 unsaturated linoleic acid, the precursor of some prostaglandins, leukotrienes, and thromboxanes, while Candida sp. and K. polysporus accumulated a high content of palmitoleic acid.
Keywords: cytosol; kvasinky; fosfáty; kultivační média; Yeasts; Phosphates; mastné kyseliny; Nitrogen; dusík; Fatty Acids; Culture Media; Cytosol